Classroom Teachers' Representations regarding the Physical Education in the School: contributions of the Program of Continuous Formation PEC-Municipals - Marcos Garcia Neira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article presents the results of a research which intended to identify the modifications that ocurred in the representations regarding the Physical education in the school of a group of classroom teachers that attended a Program of Academical Formation (named as PEC) in municipal districts. The data, obtained by the Clinical Method, were confronted with the knowledge on the construtivist learning conception and on the pedagogic tendencies of the school Physical education. As relevant discoveries we detached the following modifications: from representations that reflected a vision dualist (body/mind) to a technical vision (the body as tool) or, from the latter to the sociocultural vision (the citizen body). The identified transformations accompanied the historical path of the Physical education in Brazil.